Target induction of heme oxygenase-1 attenuates anti-HLA I antibody induced transplant vasculopathy in an allogeneic aortic transplantation model in mice. (3rd October 2022) - Kummer, L; Zaradzki, M; Stefan, K; Weigand, M A; Larmann, J
Abstract: Introduction: After solid organ transplantation every second patient develops transplant vasculopathy (TV), which still remains the major obstacle for long-term graft survival. The main risk factor for developing TV are de novo synthesized donor-specific antibodies binding molecules of the MHC complex (HLA complex in humans, respectively) on the surface of endothelial cells (EC). EC become activated, vascular smooth muscle cells proliferate, and monocytes are recruited, contributing the development of the neointima a hallmark of TV. We have demonstrated that the anti-HLA I antibody (w6/32) significantly increases transmigration of monocytes across an endothelial monolayer in vitro. These interactions were dependent on modulating the anti-inflammatory enzyme heme oxygenase (HO)-1. Purpose: The aim of the project is to investigate which adhesion molecule might mediate the antibody-induced transmigration of monocytes sensitive to HO-1 modulation and whether this modulation has beneficial effects in an allogenic aortic transplantation model in mice. Methods: Before w6/32 stimulation, HO-1 was modulated by pretreating Human Coronary Artery Endothelial Cells (HCAEC) either with CoPPIX as a HO-1 activator or with statins to test for a therapeutic approach. Expression of a variety of established adhesion receptors in HCAEC was screened after HO-1 modulation and w6/32 stimulation. Antibody-induced transmigration and adhesion of THP-1 were quantified in the presence of CD62E-blocking antibodies. Thoracic aorta was transplanted into the abdominal aorta between fully MHC mismatched mice and applying the corresponding anti-MHC I antibody (SF1-1.1) induced TV. Mice were treated with CoPPIX, statins or CORM to evaluate the effects of HO-1 modulation or its metabolite CO on TV development. Statistical evaluation was performed with t-test or ANOVA. Results: HO-1 modulation in HCAEC diminished w6/32-induced THP-1 transmigration. CD62E-expression in HCAECs was enhanced after w6/32 stimulation on mRNA and protein level, but preincubation with CoPPIX or statins reduced these effects. Incubation of HCAEC with a CD62E-blocking antibody after w6/32 stimulation significantly diminished the rate of transmigration normalized to isotype-stimulated HCAEC (isotype 100%, w6/32 + IgG 226% vs. w6/32 + CD62E-block 138%, p<0.05.). Treatment of mice with CoPPIX resulted in a significant reduction of the SF1-1.1-induced number of transmigrated monocytes (SF1-1.1: 10 vs. CoPPIX: 5.4; p<0.05). Application of statins (SF1-1.1: 10 vs. statin 6.6; p<0.05) or CORM (CORM: 6.1 vs. iCORM: 11.3, p<0.05) significantly reduces monocyte number as well. In all treatment groups, the SF1-1.1-induced neointima formation was ameliorated. Conclusion: w6/32-induced monocyte transmigration is CD62E-dependent. SF1-1.1-induced monocytic infiltrate and intimal hyperplasia in a murine aortic transplantation model is also CD62E dependent and amenable to HO-1 modulation. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This sudy was funded by the German Research Foundation to Jan Larmann